138k views
5 votes
ANSWER PLZZZZZZ!!!!!!!!!!!!!!!

ANSWER PLZZZZZZ!!!!!!!!!!!!!!!-example-1
User RolandoCC
by
5.4k points

2 Answers

5 votes

Answer:

(3x - 2)

Explanation:

Given that the area A = length × width

A = 3x² + 7x - 6 ← factor to obtain length

Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term

product = 3 × - 6 = - 18 and sum = + 7

The factors are + 9 and - 2

Use these factors to split the x- term

3x² + 9x - 2x - 6 ( factor the first/second and third/fourth terms )

= 3x(x + 3) - 2(x + 3) ← factor out (x + 3) from each term

= (x + 3)(3x - 2)

We know (x + 3) is the width , then (3x - 2) is the length

User Roshan
by
6.0k points
1 vote

Answer:

length=(3x-2)

Explanation:

area of rectangle=length*breadth

3x^2 + 7x - 6=length * (x+3)

3x^2 +(9-2)x -6=length *(x+3)

3x^2+9x-2x-6=length*(x+3)

3x(x+3)-2(x+3)=length*(x+3)

(x+3)(3x-2)=length*(x+3)

(x+3)(3x-2)/(x+3)=length

(3x-2)=length

User Pranav Pavan
by
6.0k points